Saudi Cement Industry - A Comparative Study of Profitability Position during Economic Slowdown - Dr. Shahid Husain,; Dr. Maysoon Khoja, (International Journal of Engineering and Management Research, 2021)
Infrastructure is one of the favorite projects of every developed and developing nation. Construction industry occupies a prominent place in the infrastructure development of a country. Cement is one the elementary material components in the construction industry. Saudi Arabia has shown a weaker performance in generation of revenue over a period of five years from 2015 to 2019. In a situation of economic slowdown it becomes a challenge for the business concerns to maintain their profitability. The present study is designed to analyze and compare the profitability position of cement companies in the kingdom of Saudi Arabia during this period. The study belongs to top five cement companies in terms of market value and revenue generation in the kingdom of Saudi Arabia. To measure the profitability gross profit ratio, operating ratio, operating profit ratio, net profit ratio and return on investment have been used as variables. One way anova has been used to test the hypotheses. The study shows that these companies do not differ significantly from one another in terms of gross profit, operating profit and net profit but they differ significantly when return on investment is compared. Cement companies can increase their profitability by improving the components of those ratios that have been the cause of decline in profitability.